Research on Temporal and Spatial Variation Characteristics of Eutrophication in the Xiaojiang River Basin under the Change of Water Level in the Three Gorges Reservoir Area - ZHOU Xingyue; HUANG Gang; ZHU Shujing (Renmin Zhujiang)
Since the operation of the Three Gorges Reservoir, the phytoplankton blooms in Xiaojiang River Basin has become more and more serious. This paper monitors and analyzes the change of water level in Three Gorges Reservoir area, the total nitrogen and phosphorus in Xiaojiang River Basin and the total phosphorus in phytoplankton. The results showed that: (1) The phytoplankton bloom occurs frequently when the water level in the Three Gorges Reservoir area is low (163 m) and continues to drop, and it decreases significantly when the water level is high (173 m) and continues to rise; (2)Phytoplankton blooms are easy to break out in Xiaojiang River Basin in spring; (3) The regulation of water level in the Three Gorges Reservoir area has the greatest impact on the occurrence of phytoplankton blooms in the middle reaches of Xiaojiang River Basin, followed by the upper and lower reaches. Therefore, the change of water level in the Three Gorges Reservoir area has a high correlation with the occurrence regularity of phytoplankton blooms in the Xiaojiang River Basin. The temporal and spatial distribution characteristics of phytoplankton blooms in the main tributaries of the Three Gorges Reservoir are studied under the change of its water level, which provides a basis for the identification and prevention of the phytoplankton blooms in the tributaries of the Three Gorges Reservoir area.